2020
DOI: 10.1007/s00787-020-01559-8
|View full text |Cite
|
Sign up to set email alerts
|

Guideline adherence in German routine care of children and adolescents with ADHD: an observational study

Abstract: Although guidelines for the assessment and treatment of mental disorders in childhood and adolescence have been available in Germany for several years, there are barely any data on adherence to guidelines in national routine care. Therefore, the study aimed at a nationwide evaluation of guideline adherence (GA) for the assessment and treatment of children and adolescents with attention-deficit/hyperactivity disorder (ADHD) in German routine care in various groups of health care providers (HCPs). Besides a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The association with acne and eczema found in those with ADHD may indicate an opportunity for providers to aid this unique patient population further. Patients with ADHD struggle with routine tasks, particularly those that do not have an immediate benefit (Mücke et al, 2021). Unfortunately, skincare may have a direct cost of time and effort with delayed benefits; however, dermatologists, psychiatrists, and primary care providers may overcome this uneven cost-benefit analysis perceived by patients through suitable communication.…”
Section: Discussionmentioning
confidence: 99%
“…The association with acne and eczema found in those with ADHD may indicate an opportunity for providers to aid this unique patient population further. Patients with ADHD struggle with routine tasks, particularly those that do not have an immediate benefit (Mücke et al, 2021). Unfortunately, skincare may have a direct cost of time and effort with delayed benefits; however, dermatologists, psychiatrists, and primary care providers may overcome this uneven cost-benefit analysis perceived by patients through suitable communication.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, adherence to the country’s clinical practice guideline with respect to prescribing pharmacotherapy for ADHD was very high (97.2%) in a study by Mücke et al . 12 However, another German study of nearly 20 000 initial paediatric ADHD medication claims found that, while the majority were commenced on stimulants, 13% of children were commenced on a second-line or combination of medications, rather than trialling the stimulants first. 13 In the USA, McElligott et al 14 found that all surveyed prescribers offered stimulants as first-line intervention in moderate or severe ADHD cases, but that some prescribers opted for lisdexamfetamine as the first-line intervention, rather than methylphenidate.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis et al ’s11 study did not examine the practice of psychiatrists and only examined pharmacological therapies. In Germany, adherence to the country’s clinical practice guideline with respect to prescribing pharmacotherapy for ADHD was very high (97.2%) in a study by Mücke et al 12. However, another German study of nearly 20 000 initial paediatric ADHD medication claims found that, while the majority were commenced on stimulants, 13% of children were commenced on a second-line or combination of medications, rather than trialling the stimulants first 13.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials among adolescents with ADHD suggest that they are more likely to engage with and comply with their treatment when they have an active role in the treatment process (DuPaul et al, 2020; Sibley et al, 2017). According to recent treatment guidelines, developmentally appropriate types of treatment (modalities) and adjunctive strategies that effectively incorporate adolescents’ developmental needs and preferences may increase treatment adherence and amplify the therapeutic benefits of current psychosocial interventions (DuPaul et al, 2020; Mücke et al, 2021; Wolraich et al, 2019; Zemestani et al, 2021). However, little research has been conducted on potential adjunctive modalities for augmenting the therapeutic benefits of current psychosocial interventions for adolescents with ADHD.…”
mentioning
confidence: 99%